Neue Karte des westlichens Theiles der Welt: zur Erläuterung der Seezüge der Niederländer nach Westindien zu folge den neuesten Entdeckungen. (1744)
Map shows Western Hemisphere, western Europe, western coast of Africa, "Island" [Iceland], "Groenland," British, French, and Spanish colonies in North America. Last date of discovery shown is 1743. Northwestern portion of North American continent undefined. Prime meridian: Ferro. Includes names of explorers and dates of discoveries. Relief shown pictorially. Scale not given.